Musical Sophistication and the Effect of Complexity on Auditory Discrimination in Finnish Speakers - Dawson, Caitlin; Aalto, Daniel; Šimko, Juraj; Vainio, Martti; Tervaniemi, Mari (Frontiers in Neuroscience, 2017)
Musical experiences and native language are both known to affect auditory processing. The present work aims to disentangle the influences of native language phonology and musicality on behavioural and subcortical sound feature processing in a population of musically diverse Finnish speakers as well as to investigate the specificity of enhancement from musical training. Finnish speakers are highly sensitive to duration cues since in Finnish, vowel and consonant duration determine word meaning. Using a correlational approach with a set of behavioural sound feature discrimination tasks, brainstem recordings, and a musical sophistication questionnaire, we show that Finnish speakers with more musical sophistication do not show more precise duration processing either in the auditory brainstem response or in behavioural tasks, but they do show an enhanced pitch discrimination compared to Finnish speakers with less musical experience and show greater duration modulation in a complex task. These results suggest that there may be a ceiling effect set for certain sound features which corresponds to the phonology of the native language, leaving an opportunity for music experience-based enhancement of sound features not explicitly encoded in the language (such as pitch, which is not explicitly encoded in Finnish). Finally, the pattern of duration modulation in more musically sophisticated Finnish speakers suggests integrated feature processing for greater efficiency in a real world musical situation. These results have implications for research into the specificity of plasticity in the auditory system as well as to the effects of interaction of specific language features with musical experiences.